Implementasi Nilai Bela Negara Melalui Unit Kegiatan Mahasiswa(UKM) Resimen Mahasiswa (MENWA) - Imam Suyitno; Nurharsya Khaer Hanafie; Andi Nur Indah (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2025)
Implementation of National Defense Values in the Student Activity Unit (UKM) of the Wolter Mongisidi Student Regiment (MENWA) Unit 702, Makassar State University. Thesis. Pancasila and Citizenship Education Study Program. PPKn and Business Law Department, Faculty of Social Sciences and Law. Makassar State University. Supervised by Imam Suyitno and Nurharsya Khaer Hanafie. The purpose of this study was to determine 1) the implementation of national defense values in the student activity unit of the Wolter Mongisidi Student Regiment Unit 702, Makassar State University in terms of To find out how the aspects of the Implementation of national defense values are in terms of: A. Love for the homeland; a) Willing to Sacrifice a) Soul and Body Proud as Indonesians. B. Awareness of Nation and State; a) Participate in general elections b) Think, behave and do the best for the nation and state. C. Belief in Pancasila as the nation's ideology; a) Understand the values in Pancasila b) Practice the values of Pancasila in everyday life. D. Have the initial ability to defend the country; a) Like to exercise b) Always maintain their health. 2) Inhibiting factors for the implementation of national defense values in the student activity unit of the Wolter Mongisidi Student Regiment Unit 702, Makassar State University 1) The implementation of national defense values in the student activity unit of the Wolter Mongisidi Student Regiment Unit 702, Makassar State University consists of 4 indicators, namely: A. Love for the homeland; a) Willing to Sacrifice b) Soul and Body Proud to be Indonesian. B. Awareness of Nation and State; a) Participate in general elections b) Think, behave and do the best for the nation and state. C. Belief in Pancasila as the nation's ideology; a) Understand the values in Pancasila b) Practice the values of Pancasila in everyday life. D. Having initial national defense skills; a) Likes to exercise b) Always maintains his health 2) The inhibiting factor in implementing national defense values in the student activity unit of the Wolter Mongisidi Student Regiment Unit 702, Makassar State University is that time constraints greatly affect the effectiveness of training and the achievement of program goals in Menwa, considering the importance of balance between academic responsibilities and organizational activities. For this reason, more flexible and efficient time management is needed so that training programs can run more optimally without sacrificing quality and achieving organizational goals.